Topographic Variations of Choroidal Thickness in Healthy Eyes on Swept-Source Optical Coherence Tomography - Touhami, Sara; Philippakis, Elise; Mrejen, Sarah; Couturier, Aude; Casteran, Céline; Levent, Priscille; Tadayoni, Ramin; Gaudric, Alain (Investigative ophthalmology & visual science, 2020)
To assess topographic variations of choroidal thickness (CT) in the fovea and beyond in healthy eyes. This cross-sectional study included healthy subjects ≤ 55 years of age with axial lengths (22-26 mm) and refractive error margins (-4D, +4D) in normal ranges. Images were acquired using swept-source optical coherence tomography angiography (OCT-A). Corneal thickness (CT) maps from 12 × 12-mm radial scans and 9 × 9-mm OCT-A B-scans were analyzed. The study included 64 eyes of 33 subjects (mean age, 37 years). Mean CT was >300 µm in all locations except the nasal outer macula. The subfoveal CT was >395 µm in 30% of cases; in 38.7% of cases, >50% of the CT map was thicker than 395 µm. The mean thickest choroidal point was 395.2 µm (range, 164-548 µm), located superior and temporal to the macula in 72.2% of cases and subfoveally in 1.8% of cases. The CT pattern was symmetrical (58%) or asymmetrical (42%) along a horizontal axis correlating with choroidal vein distribution. Half of the asymmetrical patterns were thicker in the inferior quadrants, with an oblique temporal watershed of venous drainage, and the other half were thicker superiorly. The mean vascularity index was ∼75% regardless of the mean CT. One-third of healthy eyes of patients younger than age 55 had a thick choroid (>395 µm). In these normal eyes, the thickest choroidal point was not subfoveal, CT symmetry above and below the fovea depended on choroidal vein distribution, and choroidal vascularity index was independent from CT. No patients demonstrated fundus autofluorescence abnormalities, and the choriocapillaris remained visible even in thick choroids. These features could be interesting when differentiating normal versus pathological states.